2013
DOI: 10.1667/rr3049.1
|View full text |Cite
|
Sign up to set email alerts
|

Filgrastim Improves Survival in Lethally Irradiated Nonhuman Primates

Abstract: Treatment of individuals exposed to potentially lethal doses of radiation is of paramount concern to health professionals and government agencies. We evaluated the efficacy of filgrastim to increase survival of nonhuman primates (NHP) exposed to an approximate mid-lethal dose (LD50/60) (7.50 Gy) of LINAC-derived photon radiation. Prior to total-body irradiation (TBI), nonhuman primates were randomized to either a control (n =22) or filgrastim-treated (n =24) cohorts. Filgrastim (10 μg/kg/d) was administered be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 45 publications
(36 reference statements)
6
161
2
Order By: Relevance
“…In our study, G-CSF resulted in 62.5% survival in the test group compared to 25% survival in the control piglets. This is comparable to 50% and 78.3% survival seen in G-CSF-treated adult minipigs at LD70/30 [11] and G-CSF treated NHPs at LD50/60, respectively [23]. G-CSF increased neutrophil counts after 24 h of administration and kinetics of neutrophil recovery were similar to those observed in pediatric cancer patients with chemotherapy induced neutropenia [24], confirming the potential of the minipig as a model for the human H-ARS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In our study, G-CSF resulted in 62.5% survival in the test group compared to 25% survival in the control piglets. This is comparable to 50% and 78.3% survival seen in G-CSF-treated adult minipigs at LD70/30 [11] and G-CSF treated NHPs at LD50/60, respectively [23]. G-CSF increased neutrophil counts after 24 h of administration and kinetics of neutrophil recovery were similar to those observed in pediatric cancer patients with chemotherapy induced neutropenia [24], confirming the potential of the minipig as a model for the human H-ARS.…”
Section: Discussionsupporting
confidence: 73%
“…Blood samples were collected once before irradiation followed by days 0, 1,3,7,10,14,17,20,23,28,35,42, and 45 post-irradiation. Blood was collected in EDTA tubes and immediately processed for complete blood counts with differentials (CBC/diffs) using the ADVIA 2120 (Siemens Medical Solutions Diagnostics, Ireland).…”
Section: Blood Sampling Indicators Of Health and Pathologymentioning
confidence: 99%
“…These data are significant, given that G-CSF is the treatment currently recommended for individuals exposed to lethal TBI [4], as supported by a single study that demonstrated a benefit for G-CSF when combined with highly intensive, trigger-based medical management [5]. By comparison, our data show that a regimen of 18 daily doses of G-CSF alone, in the absence of other supportive medical interventions, provides no survival benefit over that of the vehicle control.…”
Section: Discussionmentioning
confidence: 99%
“…Promising radiation countermeasures under development for H-ARS have been tested in NHP for efficacy and pharmacokinetics/ pharmacodynamics. Some important radiation countermeasures tested for efficacy in the NHP model include G-CSF (filgrastim, Neupogen) (Farese et al 2013;, PEGylated G-CSF (PEGfilgrastim/Neulasta) (Hankey et al 2015), CBLB502 (Entolimod) (Krivokrysenko et al 2012(Krivokrysenko et al , 2015, interleukin-12 (HemaMax) (Basile et al 2012;GluzmanPoltorak et al 2014aGluzmanPoltorak et al , 2014b, AEOL 10150 (meso-porphyrin mimetic) (Garofalo et al 2014b), 5-Androstenediol (Stickney et al 2006(Stickney et al , 2007, amifostine (WR2721, Ethyol) (Geary et al 1989), B-190 (Vasin et al 2014) and c-tocotrienol (Singh et al 2016a). …”
Section: Nhpmentioning
confidence: 99%
“…Radiomitigators include immunomodulating agents such as 5-androstenediol, interleukin-12, G-CSF, PEGylated G-CSF, GM-CSF, and CBLB502 (truncated flagellin), as well as and angiotensin-converting enzyme inhibitors (ACE; captopril) (Seed 2005;Dumont et al 2010;Singh et al 2012Singh et al , 2014aMoulder 2014). Radiation therapeutics are agents administered once symptoms manifest in order to accelerate regeneration of tissue and organs Wagemaker et al 1998;Farese et al 2001Farese et al , 2013Drouet et al 2004;Herodin et al 2007;Dumont et al 2010). G-CSF, PEGylated G-CSF, GM-CSF, and cellular therapy falls under this class (Singh et al 2015a).…”
Section: Introductionmentioning
confidence: 99%